O uso de estimulação olfativa em discriminações simples combinadas em cães domésticos - SOUZA, Liane Dahás Jorge de (Universidade Federal do Pará, 2017)
The present study sought to replicate systematically a previous article, seeking to verify functional class formation with olfactory stimuli in two domestic dogs. We conducted repeated yoked reversals of simple discriminations training, with only one pair of stimuli per trial and with greater experimental control in olfactory stimuli positioning. Despite adequate responses to reversals of function, there was no evidence for functional class formation in this study. It is argued that the required response to the dogs, the type of olfactory stimuli used, the frequency of training and the equipment used to present the stimuli may have hampered the task.